Effect of alkali doping on CIGS photovoltaic ceramic tiles. (1st May 2017) - Fraga, D.; Stoyanova Lyubenova, T.; Martí, R.; Calvet, I.; Barrachina, E.; Carda, J.B.
Graphical abstract: Highlights: Porcelain stoneware tiles as alternative substrates for CIGS thin film solar cells have been used. Different enamels compositions were investigated. Enamel act as chemical barrier. Na2 O and K2 O containing enamels act efficiently as alkali sources. Abstract: This report studies the influence of alkali elements (Na, K) on the morphological, structural, and optoelectronic properties of CIGS ceramic tile solar cells. Several ceramic enamels with altered chemical composition in terms of the amount of alkali elements have been tested and compared. The influences of the type of alkali, their amount, and transfer mechanism have been investigated. The solar cell device has been assembled and characterized. The results obtained indicate that alkali elements (combination of Na and K) modified the surface roughness, and their diffusion from the enamel toward the absorber affects the structural and final optoelectronic properties of the device. Alkali doping improves the Ga incorporation in the crystal lattice and results in an increase in open circuit voltage values, fill factor, and device efficiency. The optimal amounts of alkali have also been determined. The best conversion efficiency is achieved for the cell with 4% wt Na2 O and 3.2% wt K2 O (Eff. = 3.5%), which presents an improvement of 30% in efficiency relative to the standard solar cell sample chosen for comparative purposes.